2019
DOI: 10.1083/jcb.201807125
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of marked chromosome regions reveals their dynamic resolution and compaction in mitosis

Abstract: When human cells enter mitosis, chromosomes undergo substantial changes in their organization to resolve sister chromatids and compact chromosomes. To comprehend the timing and coordination of these events, we need to evaluate the progression of both sister chromatid resolution and chromosome compaction in one assay. Here we achieved this by analyzing changes in configuration of marked chromosome regions over time, with high spatial and temporal resolution. This assay showed that sister chromatids cycle betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 62 publications
(99 reference statements)
4
44
0
Order By: Relevance
“…Previous work suggests that the two-sided loop extrusion model can rapidly achieve 1000-fold linear compaction in the regime in which LEFs are densely loaded on the chromosome ( λ/d ≳10), which is expected for mitotic chromosomes of higher eukaryotes (Goloborodko et al, 2016b) . With a loop extrusion speed of v ≈1 kb/s (Ganji et al, 2018) , two-sided extrusion can achieve full linear compaction within one residence time (1/ k unbind ~2-10 min (Gerlich et al, 2006a;Terakawa et al, 2017;Walther et al, 2018) ) and full 3D compaction and loop maturation occurs over a few (<10) residence times (Goloborodko et al, 2016a) , consistent with the duration of prophase and / prometaphase and in vivo observations of mitotic chromosome compaction (Eykelenboom et al, 2019;Gibcus et al, 2018) and resolution (Eykelenboom et al, 2019) .…”
Section: Compaction and Resolution Of Mitotic Chromosomes Model And Osupporting
confidence: 64%
See 2 more Smart Citations
“…Previous work suggests that the two-sided loop extrusion model can rapidly achieve 1000-fold linear compaction in the regime in which LEFs are densely loaded on the chromosome ( λ/d ≳10), which is expected for mitotic chromosomes of higher eukaryotes (Goloborodko et al, 2016b) . With a loop extrusion speed of v ≈1 kb/s (Ganji et al, 2018) , two-sided extrusion can achieve full linear compaction within one residence time (1/ k unbind ~2-10 min (Gerlich et al, 2006a;Terakawa et al, 2017;Walther et al, 2018) ) and full 3D compaction and loop maturation occurs over a few (<10) residence times (Goloborodko et al, 2016a) , consistent with the duration of prophase and / prometaphase and in vivo observations of mitotic chromosome compaction (Eykelenboom et al, 2019;Gibcus et al, 2018) and resolution (Eykelenboom et al, 2019) .…”
Section: Compaction and Resolution Of Mitotic Chromosomes Model And Osupporting
confidence: 64%
“…We determined whether variants of the one-sided loop extrusion model can explain mitotic chromosome compaction and the spatial resolution of connected sister chromatids. Experimentally, it has been shown that these phenomena are driven by the condensin complex (Eykelenboom et al, 2019;Hagstrom et al, 2002;Hirano, 2016;Hirano et al, 1997;Hirano and Mitchison, 1994;Hudson et al, 2003;Nagasaka et al, 2016;Ono et al, 2003;Piskadlo et al, 2017;Shintomi et al, 2017Shintomi et al, , 2015Steffensen et al, 2001) . During mitosis, mammalian chromosomes are linearly compacted ~1000-fold, leading to the formation of rod-like chromatids.…”
Section: Compaction and Resolution Of Mitotic Chromosomes Model And Omentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by genetic manipulation within the localized region of the arrays, it is possible to specifically study and quantify the effect of the local chromosome landscape on the behavior within a chromosome region. In this way, in our experiments, we were able to investigate the role of a specific CTCF-binding site in organizing and maintaining sister chromatid cohesion as cells approach mitosis [72]. This observation has since been reaffirmed with a novel Hi-C methodology that can distinguish sequences from different sister chromosomes and define sister-sister chromosome contacts [74].…”
Section: Use Of Crispr-cas9 To Visualize Selected Chromosome Locimentioning
confidence: 60%
“…Sequence-integration methodologies for observing specific chromosomal regions in live cells by fluorescence microscopy. (a) tet-, lacor lambda operator arrays, containing between 100 and 500 repeated domains, can be targeted to specific locations using CRISPR-Cas9 DNA targeting technologies [46,72,73]. These arrays are visualized by accumulation of fluorescently-tagged TetR, LacI or lambdaCi proteins (respectively).…”
Section: Methods Of Visualizing Chromosome Loci In Live Cellsmentioning
confidence: 99%